Highly variable aerodynamic roughness length (z0) for a hummocky debris‐covered glacier. Issue 16 (23rd August 2017) - Miles, Evan S.; Steiner, Jakob F.; Brun, Fanny
Abstract: The aerodynamic roughness length ( z 0 ) is an essential parameter in surface energy balance studies, but few literature values exist for debris‐covered glaciers. We use microtopographic and aerodynamic methods to assess the spatial variability of z 0 for Lirung Glacier, Nepal. We apply structure from motion to produce digital elevation models for three nested domains: five 1 m 2 plots, a 21, 300 m 2 surface depression, and the lower 550, 000 m 2 of the debris‐mantled tongue. Wind and temperature sensor towers were installed in the vicinity of the plots within the surface depression in October 2014. We calculate z 0 according to a variety of transect‐based microtopographic parameterizations for each plot, then develop a grid version of the algorithms by aggregating data from all transects. This grid approach is applied to the surface depression digital elevation model to characterize z 0 spatial variability. The algorithms reproduce the same variability among transects and plots, but z 0 estimates vary by an order of magnitude between algorithms. Across the study depression, results from different algorithms are strongly correlated. Using Monin‐Obukov similarity theory, we derive z 0 values from the meteorological data. Using different stability criteria, we derive median values of z 0 between 0.03 m and 0.05 m, but with considerable uncertainty due to the glacier's complex topography. Considering estimates from these algorithms, results suggest that z 0 varies across Lirung Glacier between ∼0.005 m (gravels) to ∼0.5 m (boulders). Future efforts should assess the importance of such variable z 0 values in a distributed energy balance model. Key Points: Aerodynamic roughness length ( z 0 ) is highly variable for hummocky debris‐covered glaciers, ranging from 0.005 m to 0.5 m Theoretical and empirical microtopographic methods correlate but differ in magnitude (4X) and are sensitive to scale of analysis Aerodynamically derived values of z 0 (0.03–0.05 m) represent smoother surface character for this complex terrain